Does negative news reporting on the economy get reflected in companies' business situation? - David Iselin (ETH Zurich, KOF Swiss Economic Institute, 2017)
We examine the effects of negative economic news reporting on companies' self-assessment of their business situation. In order to measure this negativity effect, we introduce a new daily business indicator for the Swiss manufacturing sector and examine the influence of newspaper articles, which we scan for particular keywords, on a daily basis. We use OLS and VAR models to examine the mutual influence of negative news and the business situation of private companies. The results show a negative influence of news reporting on the self-assessment of the companies surveyed, also when controlling for the overall economic situation. However, the negative effect is not stable in all our set-ups.
Keywords: 330; Media Data; News; Business Situation